Dawning of the [Ny] = 32 shell closure seen through precision mass measurements of neutron-rich titanium isotopes - Leistenschneider, Erich; Bollig, Julian (Physical review letters, 2018)
A precision mass investigation of the neutron-rich titanium isotopes 51−55Ti was performed at TRIUMF’s Ion Trap for Atomic and Nuclear science (TITAN). The range of the measurements covers the N=32 shell closure, and the overall uncertainties of the 52−55Ti mass values were significantly reduced. Our results conclusively establish the existence of the weak shell effect at N=32, narrowing down the abrupt onset of this shell closure. Our data were compared with state-of-the-art ab initio shell model calculations which, despite very successfully describing where the N=32 shell gap is strong, overpredict its strength and extent in titanium and heavier isotones. These measurements also represent the first scientific results of TITAN using the newly commissioned multiple-reflection time-of-flight mass spectrometer, substantiated by independent measurements from TITAN’s Penning trap mass spectrometer.
Gesehen am 26.02.2020
Im Titel ist "Ny" als griechischer Buchstabe dargestellt